2022
DOI: 10.1186/s43055-022-00918-6
|View full text |Cite
|
Sign up to set email alerts
|

Value of diffusion-weighted magnetic resonance imaging (DWI) in differentiating orbital lymphoma from idiopathic orbital inflammatory pseudotumor

Abstract: Background Diffusion-weighted MR imaging can provide physiological information complementing morphological findings from conventional MRI. It detects early tissue changes associated with changes in water content, such as changes in the permeability of cell membranes, cell swelling or cell lysis. Areas of diseased tissue are highlighted with increased signal intensity on diffusion-weighted MR imaging. A decrease in the ADC is expected with increased intracellular tissue caused by either cell swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Multiple prior investigations have found that lower ADC values are consistent with malignancy, whereas higher values are consistent with inflammatory process. 10,11 ADC values in our case were consistent with inflammatory process. In addition, relatively elevated perfusion was seen in the orbital mass indicating that this lesion has increased vascular supply compared with the normal orbit, which is consistent with inflammatory and neoplastic lesions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Multiple prior investigations have found that lower ADC values are consistent with malignancy, whereas higher values are consistent with inflammatory process. 10,11 ADC values in our case were consistent with inflammatory process. In addition, relatively elevated perfusion was seen in the orbital mass indicating that this lesion has increased vascular supply compared with the normal orbit, which is consistent with inflammatory and neoplastic lesions.…”
Section: Discussionsupporting
confidence: 81%
“…ADC values can help differentiate malignancy from inflammatory processes, although significant overlap still exists. 11 Because inflammation in and around the eye may be the presenting symptom, initiating a proper workup facilitates diagnosis, which may help reduce the increased mortality associated with AAV.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic orbital inflammation (IOI) often called pseudotumor, which is the third most common orbital disease, typically cause an increase in oculomotor muscle size [11] . On MRI, IOI shows an infiltrative mass, less often a focal mass, with contrast enhancement and lacks restricted diffusion with mean ADC value of 1.15 (± 0.37) × 10 −3 mm 2 /s [11 , 12] . In contrast, RMS with strongly restricted diffusion – like this case- is usually close to extraocular muscles without enlargement of the muscle belly.…”
Section: Discussionmentioning
confidence: 99%